2008
DOI: 10.1177/0269881108097724
|View full text |Cite
|
Sign up to set email alerts
|

Low striatal serotonin transporter protein in a human polydrug MDMA (ecstasy) user: a case study

Abstract: Evidence that the widely used methamphetamine analog MDMA (3,4-methylenedioxymethamphetamine, ecstasy) might damage brain serotonin neurones in humans is derived from imaging investigations showing variably decreased binding of radioligands to the serotonin transporter (SERT), a marker of serotonin neurones. However, in humans, it is not known whether low SERT binding reflects actual loss of SERT protein itself. As this question can only be answered in post-mortem brain, we measured protein levels of SERT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…In contrast, in the MA users of the present study, we found caudate levels of the same markers to be only modestly (up to 33%) decreased. Imaging data from two different laboratories (Reneman et al 2002;McCann et al 2008b) as well as findings of our single case autopsied human brain study (Kish et al 2000(Kish et al , 2008b suggest that exposure to ecstasy might cause decreased levels of brain serotonin markers in humans but has relatively little effect on markers of the dopamine system. In contradistinction, the results of our studies suggest that brain concentrations of markers for both neurotransmitters are decreased in users of MA, but with the dopamine system affected more than that of the serotonin.…”
Section: Serotonin Marker Changes In Ma Users Vs Other Serotonin Defmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, in the MA users of the present study, we found caudate levels of the same markers to be only modestly (up to 33%) decreased. Imaging data from two different laboratories (Reneman et al 2002;McCann et al 2008b) as well as findings of our single case autopsied human brain study (Kish et al 2000(Kish et al , 2008b suggest that exposure to ecstasy might cause decreased levels of brain serotonin markers in humans but has relatively little effect on markers of the dopamine system. In contradistinction, the results of our studies suggest that brain concentrations of markers for both neurotransmitters are decreased in users of MA, but with the dopamine system affected more than that of the serotonin.…”
Section: Serotonin Marker Changes In Ma Users Vs Other Serotonin Defmentioning
confidence: 58%
“…The uncorrected P values for two-tailed Student's t tests in each brain region are also given in brain of a single chronic high-dose user of ecstasy (Kish et al 2008b). In both conditions, PET imaging data show some loss of brain SERT binding although there is not yet consensus on the regional profile of the changes (PD- Kerenyi et al 2003;Guttman et al 2007;Albin et al 2008;ecstasy users-McCann et al 1998becstasy users-McCann et al , 2005ecstasy users-McCann et al , 2008bBuchert et al 2007;Kish et al 2007).…”
Section: Serotonin Marker Changes In Ma Users Vs Other Serotonin Defmentioning
confidence: 99%
“…To our knowledge, there are only two studies in which markers of brain 5-HT integrity have been directly assessed in human MDMA users (Kish et al, 2000(Kish et al, , 2010a. These postmortem case studies found reductions in 5-HT, SERT, and TPH in deceased MDMA users that had recently used the drug.…”
Section: Humansmentioning
confidence: 99%
“…Furthermore, the ecstasy group, although ‘grossly behaviorally normal’, reported altered mood and demonstrated generally modest deficits on some tests of attention, executive function and memory associated with SERT decrease. The direct measurement of major brain 5-HT markers in human ecstasy users was also accomplished, for the first time, in a single post-mortem brain of a high-dose user [102]. The authors showed marked decreased levels of all 5-HT neuron markers: 5-HT and 5-HIAA content and protein concentrations of its rate limiting biosynthetic enzyme, tryptophan hydroxylase and of SERT [102].…”
Section: Toxicologymentioning
confidence: 99%
“…The direct measurement of major brain 5-HT markers in human ecstasy users was also accomplished, for the first time, in a single post-mortem brain of a high-dose user [102]. The authors showed marked decreased levels of all 5-HT neuron markers: 5-HT and 5-HIAA content and protein concentrations of its rate limiting biosynthetic enzyme, tryptophan hydroxylase and of SERT [102]. These studies, therefore, appear to confirm the initial interpretation that serotonergic neurotransmission is subject to long lasting and subtle alterations following MDMA abuse in humans.…”
Section: Toxicologymentioning
confidence: 99%